Development of an integrated system of solution for decision support of crop health diagnosis : case of a machine learning enabled unmanned aerial vehicle - Ayomoh, Michael (University of Pretoria, 2023)
Dissertation (MSc(Industrial and Systems Engineering))--University of Pretoria, 2023.